Benzodiazepine dependence in subjects with alcohol use disorders: what prevalence?. Issue 10 (2nd October 2016) - Morel, A.; Grall-Bronnec, M.; Bulteau, S.; Chauvin-Grelier, P.; Gailledrat, L.; Pinot, M. L.; Jolliet, P.; Victorri-Vigneau, C.
ABSTRACT: Objective : To our knowledge, no studies have been conducted in France on benzodiazepine (BZD) dependence among outpatients with alcohol use disorders (AUD). Some international studies have been conducted on the consumption of BZD in this specific population, but the comparisons among them are difficult. We aimed to assess the current prevalence of probable benzodiazepine and BZD-like hypnotics (Z-drugs) dependence among outpatients seeking treatment for AUD. Methods : Participants were patients seeking treatment for AUD for the first time or repeating treatment after more than twelve months. Recruitment took place in seven addiction centres between January and December 2013 in the Nantes region (France). BZD/Z-drug dependence was assessed according to the DSM-IV diagnostic criteria for dependence. This information was gathered through a self-report questionnaire. Results : Among the 1005 patients included in this study, 413 were BZD/Z-drug users (41.1%). Among the 413 patients, 217 were probably dependent on at least one substance, which represents 21.6% of the total population and 52.5% of BZD/Z-drug users. Conclusion : BZD/Z-drug dependence represents a public health concern. Prescribers should take the risks into account and keep treatment courses to a minimum.